DIGITAL SERVICE MANAGEMENT EMERGENCY MODEL KALACAK 119 - puji Isyanto; Marceilla Suryana (Universitas Dharma Wacana, 2022)
Services to the community really need good skills and performance. The purpose of this study is to examine the implementation of the Kalacak 119 emergency service management model. The benefit of this study is to provide alternative solutions to community problems regarding the implementation of a fast and effective emergency service management model. This research method uses a descriptive phenomenon method, which describes the conditions that occur in people's lives about emergency service management. That improving digital the quality of services to the community that is fast and precise is a model of emergency management services that continues to develop and needs innovation and creativity. The results of this study indicate that the emergency service management model through the Kalacak 119 call center can be applied in an integrated manner, but it still needs socialization and development of a service management model to help people get emergency services